Scheme for a socio-legal study of assisted negotiation in Italy (Società e diritti, 2019)
The author critically analyzes the first static results of the negotiation agreements drawn up by the National Forensic Council, to suggest new strands of socio-juridical research able to enhance the emerging phenomenon of "forensic jurisdiction" and to make the role of lawyers understand as specialized legal actors able to direct the private legal systems, to which the ADR belong, towards the acquisition of more democratic and equitable characteristics. Such studies are also useful for guiding the choices of the Legislature that in our country seems to be trying to change procedural models developed abroad (such as the French participatory procedure, the Canadian delegated arbitration and more generally the US Collaborative Law) without a prior analysis of the conditions that can make these institutions more consistent with the national legal culture and more effective their impact on society.Key words: Negotiation, Altarnative Dispute Resolution, civil procedure